2019
DOI: 10.3389/fbioe.2019.00322
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Post-stroke Upper Limb Rehabilitation Wearable Sensor for Use in Sub-Saharan Africa: A Pilot Validation Study

Abstract: The development of context-appropriate sensor technologies could alleviate the significant burden of stroke in Sub-Saharan African rehabilitation clinicians and health care facilities. However, many commercially available wearable sensors are beyond the financial capabilities of the majority of African persons. In this study, we evaluated the concurrent validity of a low-cost wearable sensor (i.e., the outREACH sensor) to measure upper limb movement kinematics of 31 healthy persons, using an 8-camera Vicon mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…With this in mind, future work will employ a user-centered approach to design a simple, clear, and culturally relevant mobile application available in both English and Amharic (official language of Ethiopia). In addition, we will work to refine the algorithms and integrate them with the outREACH mobile application (15,(29)(30)(31) so that upper limb kinematics can be characterized on-line. Despite the numerous barriers for individuals with acquired brain injury, participants provided overall positive feedback regarding the possibility to continue post-acquired brain injury care in their home environment with the outREACH sensor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With this in mind, future work will employ a user-centered approach to design a simple, clear, and culturally relevant mobile application available in both English and Amharic (official language of Ethiopia). In addition, we will work to refine the algorithms and integrate them with the outREACH mobile application (15,(29)(30)(31) so that upper limb kinematics can be characterized on-line. Despite the numerous barriers for individuals with acquired brain injury, participants provided overall positive feedback regarding the possibility to continue post-acquired brain injury care in their home environment with the outREACH sensor.…”
Section: Discussionmentioning
confidence: 99%
“…The issues surrounding traditional upper limb physical rehabilitation has stimulated particular interest in using wearable sensors for the evaluation post-acquired brain injured upper limb dysfunction (15)(16)(17)(18). For example, 12 examined the relationship between stroke impairment level (as measured by the Fugl-Meyer assessment for upper extremity [uFMA] scores) and upper limb kinematics using a 17-sensor system (MVN, Xsens Technologies).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another enabling technology are inertial measurement units (IMUs) that exhibit great potential as a low-cost, portable means to evaluate and monitor patient progress during decentralized rehabilitation protocols ( Parrington et al, 2021 ). IMUs have been shown to accurately measure motor function and provide information regarding the different motor components that contribute to task performance, (e.g., movement accuracy, efficiency, precision, smoothness) ( Hughes et al, 2019a ; Schwarz et al, 2019 ), with kinematic variables obtained by IMU-based system correlating with standard clinical assessments ( Hughes et al, 2019b ; Oubre et al, 2020 ; Chen et al, 2021 ). For example, Hughes et al (2019a) , Hughes et al (2019b) developed a low-cost IMU-based wearable sensor specifically designed for medically underserved populations.…”
Section: Introductionmentioning
confidence: 99%
“…Using FES, they observed that there is an increase in shoulder flexion and elbow extension. Hughes et al [ 37 ] examined the total movement time, maximum velocity, and spectral spectrum in post-stroke patients (in the ARAT block, drink, and pour water tasks) and found a very high correlation and concordance. Finally, the importance of movement analysis measures for post-stroke patients was highlighted by Lane et al [ 33 ] as objective information on the performance and progress of therapy.…”
Section: Introductionmentioning
confidence: 99%